Clinical management of community acquired pneumonia in the elderly patient. (1st November 2016) - Cilloniz, Catia; Ceccato, Adrian; San Jose, Alicia; Torres, Antoni
ABSTRACT: Introduction: Community acquired pneumonia (CAP) is a major health problem in elderly persons and is associated with high morbidity and mortality. Areas covered: This article reviews the most recent publications relative to CAP in the elderly population, with a focus on epidemiology, prognostic factors, microbial etiology, therapy and prevention. The data discussed in this review were mainly obtained from a non-systematic review using Medline, and references from relevant articles. Expert commentary: CAP can occur at any age, but its incidence and risk of death are linked to increasing age. Age-related changes in the immune system make this population more vulnerable to CAP. Mortality in hospitalized patients with CAP ranges from 10% to 12%. However, in the case of elderly patients, several studies have reported mortality rates of up to 25%. Pneumococcal and influenza vaccination comprise one of the most important preventive approaches for CAP in the elderly.